Catalogue and bibliography of Afrotropical Psychodidae: Bruchomyiinae, Psychodinae, Sycoracinae and Trichomyiinae - Kvifte, Gunnar Mikalsen (Zootaxa, 2012)
The Afrotropical fauna of Psychodidae, subfamilies Bruchomyiinae, Psychodinae, Sycoracinae and Trichomyiinae is cat-alogued. A total of 174 species in 27 genera are listed with full bibliographic citations and distributional data. Cryptotel-matoscopus Vaillant, 1982 is placed as a subgenus of Clogmia Enderlein, 1935, stat.nov.; Karakovounimerus Ježek, 1990is placed as a subgenus of Panimerus Eaton, 1904, stat.nov.; Orgaoclogmia Ježek & van Harten, 1996 is synonymisedwith Cryptotelmatoscopus Vaillant, 1982, syn.nov.; and Rhipidopsychoda Vaillant, 1991 is synonymised with ThreticusEaton, 1904 syn.nov. Telmatoscopus flagellifer Freeman, 1949, Mormia soelii Wagner & Andersen, 2007 and Rhad-inoscopus triangulatus Wagner, 1979 are transferred to Hemimormia Krek, 1971, comb.nov.; Telmatoscopus fuscipennisTonnoir, 1920 and Orgaoclogmia caboverdeana Ježek & van Harten, 1996 are transferred to Clogmia Enderlein, 1937,comb.nov.; Telmatoscopus pilosternatus Satchell, 1955 is transferred to Mormopericomiella Ježek & van Harten, 2002,comb.nov.; Copropsychoda bulbosa Ježek & van Harten, 2005, Falsologima verrucosa Ježek & van Harten, 2005, Psy-chana rujumensis Ježek & van Harten, 2005 and Psychodocha khoralkhwairensis Ježek & van Harten, 2009 are trans-ferred to Psychoda Latreille, 1796 comb.nov.; and Psychoda boettgeri Wagner, 1979 is transferred to Threticus Eaton, 1904 comb.nov. All nomenclatural changes are discussed.